The Effect of Setbacks on Interior Daylighting in Residential Buildings in Vijayawada, India - M. Kranti Kumar (Current Overview on Science and Technology Research Vol. 5, 2022)
Efficient day lighting in residential buildings provides different physiological and psychological advantages, specifically in terms of visual comfort. Day lighting is one of the key design considerations of modern architecture. Setbacks and window openings play a crucial role in allowing natural light into structures. However, many interior rooms commonly suffer from insufficient day lighting due to inadequate setbacks and window sizes. Given this context, this article is an academic endeavour to assess the impact of building setbacks on window sizes in order to achieve pleasant day lighting. Day lighting in two differently orientated independent residential buildings in Vijayawada (India) with various setbacks was studied for this purpose. The day lighting contours were computed using a Lux Meter at various times of the day in each of the buildings’ functional spaces/rooms. In addition, the interior natural lighting levels in various rooms of the buildings were compared to the needed standard illumination levels as suggested by The National Building Code of India 2005 and the local building bylaws. The places inside buildings with insufficient day lighting were detected. Based on the day lighting analysis, design suggestions for window sizes were made with regard to the individual building setbacks.